Pengaruh Pengetahuan, Lokasi dan Promosi Terhadap Minat Masyarakat Menggunakan Bank Syariah Indonesia - Trimulato Trimulato; Atikah Widhiana Putri; Ismawati Ismawati (Program Study Islamic Banking, Faculty of Economics and Bussiness Islam, State Islamic Institute of Manado (IAIN) Manado, 2022)
This study aims to determine the partial and simultaneous effect of knowledge, location, promotion on public interest in using wadiah savings products at Bank Syariah Indonesia (case study in West Sinjai sub-district). This study uses quantitative methods with a statistical approach. Sources of data used in this study is primary data. Data collection techniques This study uses the method of distributing questionnaires to users of Indonesian Islamic Bank products who are domiciled in the West Sinjai sub-district. The sample in this study includes 55 users of wadiah savings products at Islamic banks in West Sinjai District. The data analysis technique used in this research is multiple linear regression analysis. The results of this study partially show that the knowledge variable has a significant effect on people's interest in using wadiah savings products with a sig value of 0.002 <0.05. Likewise, the promotion variable has a significant effect on people's interest in using wadiah savings products with a sig value of 0.000 <0.05. The location variable has no significant effect on people's interest in using wadiah savings products with a sig value of 0.663 > 0.05. Simultaneously the variables of knowledge, location, promotion have a significant effect on people's interest in using wadiah savings products with an effect of 80.3%.